The Effect Of Information Asymmetry To Cost Of Equity Capital (Study On Manufacturing Companies Listed In Indonesia Stock Exchange For The Year 2017-2019) - et. al., Rita Yuniarti, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research focuses on the Effect of Information Asymmetry to Cost of Equity Capital in Manufacturing Companies Listed in Indonesia Stock Exchange for the year 2017-2019. The problem faced in this study is fluctuating cost of equity capital. The purpose of this study is to determine the effect of information asymmetry on the cost of equity capital in manufacturing companies listed in the Indonesia Stock Exchange 2017-2019. The method used in this research is explanatory. The result show that information asymmetry has a positive and significant effect on the cost of equity capital. This means that if the asymmetry increases, the cost of equity capital will also increase.